Genotyping of coeliac-specific human leucocyte antigen in children with type 1 diabetes: does this screening method make sense?. Issue 7 (30th December 2016) - Binder, Elisabeth; Loinger, Martina; Mühlbacher, Annelies; Edlinger, Michael; Steichen, Elisabeth; Meraner, Dagmar; Loacker, Lorin; Weigel, Guenter; Müller, Thomas; Fröhlich-Reiterer, Elke; Hofer, Sabine E
Abstract : Objectives: Due to a high linkage disequilibrium of diabetes and coeliac-specific human leucocyte antigen (HLA) genotypes, the prevalence of coeliac disease (CD) in children and adolescents with diabetes mellitus type 1 (T1D) is much higher than in the general population. Recently, the European Society for Paediatric Gastroenterology, Hepatology and Nutrition (ESPGHAN) revised new screening guidelines in which genotyping for coeliac-specific HLA alleles is recommended for high-risk patients as patients with T1D. The aim of our study was to investigate the frequency and distribution of coeliac-specific HLA genotypes in paediatric patients with T1D. Study design: HLA genotyping was performed on paediatric patients with T1D, recruited at the Medical University Hospital of Innsbruck and Graz. The test was done by PCR. Statistical analysis was performed with IBM-SPSS V.20. Results: In 121 paediatric patients with T1D (52% male), mean age 13.3 (SD 3.9) years, mean age at diabetes diagnosis 7.4 (SD 3.8) and mean diabetes duration of 5.9 (SD 3.3) years, HLA genotyping was conducted. Ninety-two per cent showed positive HLA DQ2 and/or HLA DQ8 genotypes. Thirty-four per cent carried HLA DQ2, 33% were HLA DQ2+DQ8 positive and 25% of the patients showed positive results for HLA DQ8 alone. Only 8% had no coeliac-specific HLA markers. Four (3%) patients were diagnosed with CD. Conclusions: The majority of paediatric patients with T1D has positive coeliac-specific HLA genotypes DQ2 and/or DQ8. Therefore, genotyping for coeliac-specific HLA alleles as a first-line test in patients with T1D as recommended in the ESPGHAN guidelines does not seem reasonable. Screening for coeliac-specific antibodies needs to be performed on a regular basis for patients with T1D.